Optimalisasi Kegiatan KALIMASADA Terhadap Kesadaran Ketertiban Dokumen Administrasi Kependudukan Warga Di Kelurahan Petemon Kota Surabaya - Widya Dharmawan; Tukiman Tukiman (Politeknik Kampar, 2023)
KALIMASADA or an abbreviation of Population Administration Aware Community Environmental Area is an innovation from the Surabaya City Government which aims to make it easier for the community to arrange population administration documents, by involving the RT head as the RT KALIMASADA pilot and the Surabaya Great Cadre (KSH) with the closest reach to residents. With It is hoped that it will be easier for the community to provide administration services at the RT level because they are closer in terms of processing and completing the need for residence documents. The methodology that will be used by the author is qualitative, namely by making direct observations in the field, interviewing sources and related parties, as well as studying documents as a complement to the required data. First, the writer will go down to the field to see the progress of the KALIMASADA program in the Petemon Village where the writer is assigned. The focus of this service is optimizing the KALIMASADA program to support an orderly adminduk community, especially in the Petemon Village. The results of community service in the form of socialization and communication as well as orderly society in fulfilling the needs for population documents will be able to optimize the KALIMASADA program so that the KALIMASADA program activities will make the Petemon Village and the City of Surabaya become examples and be better than before.